2024
DOI: 10.1126/scitranslmed.adk9129
|View full text |Cite
|
Sign up to set email alerts
|

Increased β 2 -adrenergic signaling promotes fracture healing through callus neovascularization in mice

Denise Jahn,
Paul Richard Knapstein,
Ellen Otto
et al.

Abstract: Traumatic brain injury (TBI) leads to skeletal changes, including bone loss in the unfractured skeleton, and paradoxically accelerates healing of bone fractures; however, the mechanisms remain unclear. TBI is associated with a hyperadrenergic state characterized by increased norepinephrine release. Here, we identified the β 2 -adrenergic receptor (ADRB2) as a mediator of skeletal changes in response to increased norepinephrine. In a murine model of femoral osteotomy combined with cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 72 publications
1
2
0
Order By: Relevance
“…Histological analysis of bone tissue at 42 dpi revealed increased bone formation in CCI+FF mice as compared to FF mice. This observation is consistent with previous findings from clinical and experimental studies [11,12,23,26,42]. We further observed fractureinduced up-regulation of gene markers associated with bone mineralization, metabolism and remodeling, i.e., Alpl, Ibsp, and Spp1, encoding for alkaline phosphatase, BSP, and osteopontin, respectively.…”
Section: Bone Formation In the Fractured Femur Is Increased By Concom...supporting
confidence: 93%
See 2 more Smart Citations
“…Histological analysis of bone tissue at 42 dpi revealed increased bone formation in CCI+FF mice as compared to FF mice. This observation is consistent with previous findings from clinical and experimental studies [11,12,23,26,42]. We further observed fractureinduced up-regulation of gene markers associated with bone mineralization, metabolism and remodeling, i.e., Alpl, Ibsp, and Spp1, encoding for alkaline phosphatase, BSP, and osteopontin, respectively.…”
Section: Bone Formation In the Fractured Femur Is Increased By Concom...supporting
confidence: 93%
“…Both clinical observations and experimental data from animal studies indicated reciprocal brain-bone interactions [6][7][8][9]. However, most studies focused on either brain injury [40] or bone fracture [23,41] and consider the other merely a necessary co-factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation